RNA Exosome - Jensen, Torben Heick (Advances in experimental medicine and biology, 2010)
Assembling work by prominent researchers in the field of RNA exosomes, this excellent introduction to the fascinating protein complex provides a comprehensive account of the proteins' many functions as well as a historical account of the field's development.
Description based on publisher supplied metadata and other sources